Storytelling Sebagai Strategi Kampanye Non-Komersial Dalam Pelatihan Peningkatan Keterampilan Komunikasi Publik Di Kabupaten Lombok Barat - Ni Putu Sinta Dewi; I Made Agus Artana (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This community service program aims to enhance the public communication skills of the target participants through the application of storytelling as a non-commercial campaign strategy. The main problem addressed is the limited ability of participants to construct persuasive, contextual, and impactful narratives that are relevant to social issues within their communities. The implementation method employs a participatory–practice-based approach that integrates training sessions, hands-on practice, and measurable evaluation. The program begins with a needs assessment using pre-training questionnaires, followed by the delivery of materials on public communication, storytelling principles, persuasive narrative techniques, and digital media–based non-commercial campaign strategies. Evaluation is conducted through pre-tests and post-tests, skill observation, and assessment of campaign narrative outputs. The results indicate a significant improvement in participants’ cognitive, affective, and conative aspects, particularly in their ability to develop campaign narratives that are relevant, emotionally engaging, and grounded in local cultural contexts. In addition, the program fosters positive attitudinal changes and participants’ readiness to implement storytelling in public communication activities. This community service initiative provides a practical contribution to strengthening community communication capacity and has the potential to be further developed through sustained mentoring and digital media integration to broaden its social impact.